CRISPR/Cas9 Mediated Disruption of the Swedish APP Allele as a Therapeutic Approach for Early-Onset Alzheimer's Disease - Bence György; Camilla Lööv; Mikołaj P. Zaborowski; Shuko Takeda; Benjamin P. Kleinstiver; Caitlin Commins; Ksenia Kastanenka; Dakai Mu; Adrienn Volak; Vilmantas Giedraitis; Lars Lannfelt; Casey A. Maguire; et al. (Elsevier, 2018)
The APPswe (Swedish) mutation in the amyloid precursor protein (APP) gene causes dominantly inherited Alzheimer's disease (AD) as a result of increased β-secretase cleavage of the amyloid-β (Aβ) precursor protein. This leads to abnormally high Aβ levels, not only in brain but also in peripheral tissues of mutation carriers. Here, we selectively disrupted the human mutant APPSW allele using CRISPR. By applying CRISPR/Cas9 from Streptococcus pyogenes, we generated allele-specific deletions of either APPSW or APPWT. As measured by ELISA, conditioned media of targeted patient-derived fibroblasts displayed an approximate 60% reduction in secreted Aβ. Next, coding sequences for the APPSW-specific guide RNA (gRNA) and Cas9 were packaged into separate adeno-associated viral (AAV) vectors. Site-specific indel formation was achieved both in primary neurons isolated from APPSW transgenic mouse embryos (Tg2576) and after co-injection of these vectors into hippocampus of adult mice. Taken together, we here present proof-of-concept data that CRISPR/Cas9 can selectively disrupt the APPSW allele both ex vivo and in vivo-and thereby decrease pathogenic Aβ. Hence, this system may have the potential to be developed as a tool for gene therapy against AD caused by APPswe and other point mutations associated with increased Aβ.